(untitled) (El-Wahat Journal for Research and Studies, 2025)
The Researcher Discussed In This Study, Lexical Cohesion In The Narration Of The Implications Of The Conscience Of The Author By Al-Osta, And The Researcher Reached A Number Of Results, Because The Collocation Is The Highest Percentage Than The Reiteration, And That The Repetition Of The Lexical Component Is More In Number Of Cases, And The Researcher Recommended In Teaching The Novel In The Arabic Version For Speakers Of Others, As It Is A Tight Novel. Key Words: Lexical Cohesion, Collocation ,Reiteration,Topic Sentences